Algeria : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Algeria. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Algeria continues to face important challenges posed by the fall in oil prices four years ago. Despite a sizeable fiscal consolidation in 2017, the fiscal and current account deficits remain large. Real GDP growth slowed sharply, mainly driven by a contraction in hydrocarbon production, although growth in the nonhydrocarbon sector was stable. Unemployment increased to 11.7 percent in September 2017 from 10.5 in September 2016 and remains particularly high among the youth and women. Average inflation declined from 6.4 percent in 2016 to 5.6 percent owing to slowing inflation for manufactured goods and services, and stood at 3.4 percent year-over-year in April 2018.